An Analysis of Impoliteness Strategies in “The Devil Wears Prada” Movie - Rizqi, Nurhana Tri; Afriana, Afriana (Humanitatis : Journal of Language and Literature, 2025)
This research analyzes the impoliteness strategies used in “The Devil Wears Prada” movie, focusing on how these strategies reflect the power dynamics and emotional tensions between characters. By exploring examples of bald on-record impoliteness, positive and negative impoliteness, sarcasm or mock politeness, and withholding politeness, the study intends to reveal the implications of these strategies on the characters’ interactions, self-perception, and the overarching themes of ambition and identity in the film. This research utilized a descriptive qualitative method. Data was collected through observational and non-participatory techniques. The researcher observed the dialogue from the movie "The Devil Wears Prada" and recorded the data using note-taking. The non-participatory technique was employed because the researcher did not directly engage as a participant in the conversations. The analysis was conducted using the pragmatics identity method. The analysis reveals two instances of bald on record impoliteness, two instances of positive impoliteness, two instances of negative impoliteness, two instances of sarcasm or mock politeness, and one instance of withheld politeness. In examining the impoliteness strategies utilized in “The Devil Wears Prada”, it becomes clear that the characters often employ various methods to exert power and control in their interactions. Miranda Priestly, in particular, uses direct insults, sarcasm, and dismissive remarks to establish her dominance and reinforce the existing social hierarchies within the workplace. Furthermore, the film demonstrates that these strategies highlight the ruthless nature of the fashion industry and influence character development and audience interpretation. Ultimately, the dynamics of impoliteness enhance the film’s themes of ambition, sacrifice, and the ethical dilemmas found in professional settings.